The role of family risk attitudes in education and intergenerational mobility: An empirical analysis - Mathias Huebener (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper analyses the role of family risk attitudes in intergenerational mobility in incomes and education. Based on 1984-2009 data of sons and fathers from the German Socio-Economic Panel Survey, there is evidence suggesting that sons with risk taking fathers have a significantly higher educational mobility and persistently higher income mobility than peers with risk averse fathers. They obtain significantly higher levels of education, which would be justified by modest evidence on higher returns to education. The relationship seems more complex for sons' own risk attitudes. Risk taking sons experience higher educational mobility, but there is no difference in income mobility to risk averse sons. There are no considerable differences in the levels of education, but modest evidence suggesting lower returns to education for risk taking sons. The findings improve the understanding of the intergenerational transmission mechanism of economic status and show that family risk attitudes impact economic mobility. The study suggests an important intergenerational link between fathers' risk attitudes and sons' levels of education, which has not received much attention in the literature.
Keywords: D1; D8; I24; J13; J24; J62; 330; risk preferences; intergenerational mobility; educational mobility; social mobility; returns to education; intergenerational income elasticity; educational choice under uncertainty; SOEP